2012
DOI: 10.1016/j.ijid.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Betel quid use in relation to infectious disease outcomes in Cambodia

Abstract: Summary Objectives The habitual chewing of betel quid (areca nut, betel leaf, tobacco) is estimated to occur among 600 million persons in Asia and the Asia-Pacific Region. Emerging data from rural Asia indicate that the betel quid is part of traditional medicine practices that promote its use for a wide range of ailments, including infectious disease. In the present study, we examined the association between betel quid, traditional medicine, and infectious disease outcomes. Methods For the purpose of a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…Finally, in the same sample of Cambodian women that we studied, Singh et al 40 have recently reported an association between female betel quid use and infectious disease (HIV/AIDs, typhoid, dengue fever, and malaria). The link was not thought to be directly causal but rather a consequence of the effect of this habit on suppressing the immune system and, through constant injury to the oral mucosa, providing a route of entry for the pathogen.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, in the same sample of Cambodian women that we studied, Singh et al 40 have recently reported an association between female betel quid use and infectious disease (HIV/AIDs, typhoid, dengue fever, and malaria). The link was not thought to be directly causal but rather a consequence of the effect of this habit on suppressing the immune system and, through constant injury to the oral mucosa, providing a route of entry for the pathogen.…”
Section: Discussionmentioning
confidence: 55%
“…Among women and ethnic minorities of Cambodia and the region there is also a possible link between non-cigarette forms of tobacco (i.e. betel quid, waterpipe) and TB and/or lung damage [10,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…The latter is frequently shared between chewers; this, and mucosal inflammation secondary to chewing, may facilitate pneumococcal colonization. Chewing has already been associated with tuberculosis (42).…”
Section: Discussionmentioning
confidence: 99%